The athlete`s heart: insights from echocardiography - Flanagan, H.; Cooper, R.; George, K. P.; Augustine, D. X.; Malhotra, A.; Paton, M. F.; Robinson, S.; Oxborough, D. (Echo Research & Practice, 2023)
The manifestations of the athlete`s heart can create diagnostic challenges during an echocardiographic assessment. The classifications of the morphological and functional changes induced by sport participation are often beyond `normal limits` making it imperative to identify any overlap between pathology and normal physiology. The phenotype of the athlete`s heart is not exclusive to one chamber or function. Therefore, in this narrative review, we consider the effects of sporting discipline and training volume on the holistic athlete`s heart, as well as demographic factors including ethnicity, body size, sex, and age.